FRUIT AND VEGETABLE CONSUMPTION TRENDS AMONG THE FEMALE UNIVERSITY STUDENTS IN SAUDI ARABIA - Suneetha Epuru; Ala’a Eideh; Al Anoud Al Bayoudh; Eyad Alshammari (European Scientific Journal, ESJ, 2014)
Epidemiological data worldwide is in support of increasing scientificevidence that sufficient consumption of fruits and vegetables (FV) reducesthe risk of major non communicable diseases. Populations have diverse foodavailability and preferences and cultural considerations for FV consumption.Knowledge of actual consumption of FV among younger populations helpsin framing strategies to achieve potential health benefits for their future life.This study aimed at assessing the FV consumption patterns in a sample offemale students from the University of Hail.A cross sectional survey was planned to evaluate FV consumption patternsamong university students through a previously standardized selfadministeredquestionnaire for questions related to their preferences,knowledge of health benefits and frequency of consumption of FV alongwith self-reported height and weight. A total of 200 females (mean ±standard deviation (SD): age: 21.49 ± 1.72 years; height: 160.93 ± 7.68 cm;weight: 64.30 ± 12.52 kg; and BMI: 24.81 ± 4.51 kg/m2) participated. Thepercentage of subjects who likes fruits (86 %) is significantly higher (χ2=31.999; p <0.0001) as compared to the percentage of subjects who likesvegetables (71 %). There was two times higher risk for obesity for studypopulation with low vegetable consumption as compared to high vegetableconsumption (χ2= 6.123; p =0.013; OR=2.176 (CI- 1.169- 4.051)). Resultsfrom this study highlight the importance of early identification of the healthrisk behaviors in young adults and the need to promote healthy dietaryawareness and interventions.